THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE MEDIATED BY AFFECTIVE COMMITMENTS AT MUHAMMADIYAH UNIVERSITY, YOGYAKARTA - Rohana Nur Aini; Heru Kurnianto Tjahjono; Meika Kurnia Puji Rahayu D.A (International Journal Labs, 2022)
One of the important discussions related to human resources is the aspect of performance because it will determine the success of an organization. This study aims to analyze the mediating role of affective commitment on the effect of perceived organizational support on employee performance. Respondents in this study were permanent employees of the University of Muhammadiyah Yogyakarta. The samples used were 144 which were selected using purposive sampling technique. Data analysis used the Structural Equation Modeling (SEM) method with Analysis Moment of Structural (AMOS) 24.0 software. This study found that perceived organizational support had a significant direct effect on performance. This study also shows that the perceived organizational support has a significant effect on affective commitment, and there is a significant effect between affective commitment on performance. The findings of this study indicate that affective commitment has not been able to mediate perceived organizational support for performance. Recommendations for leaders, employees, and future research are discussed.